Chemical Constituents of Callistemon subulatus and Their Anti-Pancreatic Cancer Activity against Human PANC-1 Cell Line - Juthamart Maneenet; Ahmed M. Tawila; Ashraf M. Omar; Nguyen Duy Phan; Chiharu Ojima; Masahiro Kuroda; Mao Sato; Mio Mizoguchi; Ikue Takahashi; Suresh Awale (Plants, 2022)
An n-hexane extract of Callistemon subulatus was found to exhibit potent cytotoxicity against PANC-1 human pancreatic cancer cells, preferentially under nutrition starvation conditions, with a PC50 value of 6.2 µg/mL. Phytochemical investigation of this bioactive extract resulted in the isolation of fifteen compounds (1–15), including a new compound, subulatone A (–). The structure of compound 1 was elucidated using HRFABMS and NMR spectroscopic analyses. The isolated compounds were tested for their preferential cytotoxicity against the PANC-1 human pancreatic cancer cell line, using an anti-austerity strategy. Among these, myrtucommulone A (2) showed highly potent preferential cytotoxicity, with a PC50 value of 0.28 µM. Myrtucommulone A (2) was found to alter PANC-1 cell morphology, inhibit cell migration, and downregulate the PI3K/Akt/mTOR and autophagy signaling pathways in nutrient-deprived media, leading to cancer cell death. Therefore, myrtucommulone A (2) is a lead compound for anticancer drug development based on an anti-austerity strategy.